In situ measurements of strongly interacting Lithium system - Baldolini, Daniele (2018)
In this thesis, a stable device for the production of a 6Li2 molecular BEC is presented. Lithium atoms are slowed down by a Zeeman Slower and 10^8 atoms are trapped in a Magneto Optical Trap. Of these, ∼ 10^6 atoms are transferred in a red detuned Dipole Trap and an evaporation stage follows, where molecules are formed by tuning interactions via Feshbach resonances. At the end of the evaporation, a condensate containing ∼ 10^4 molecules is produced. The condensate is thus analyzed using both the standard Time of Flight technique and the in situ technique, where interactions between the condensate and thermal part are taken into account. In this description, two models are discussed: the semi-ideal approximation and the Hartree-Fock model. The difference between the two models is discussed and supported by experimental data. Furthermore, the possibility of implementing a Sub-Doppler cooling system for lithium based on the D1 Gray molasses technique is analyzed and a preliminary realization is discussed.